Keragaan Usahatani Pandan Wangi ( Pandanus amaryllifolius roxb) di Subak Tegenungan Desa Kemenuh Kecamatan Sukawati Kabupaten Gianyar - MATALIANA, GUSTI NGURAH ABUNG; YUDHARI, I DEWA AYU SRI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.1, Januari 2015, 2016)
ABSTRACT Main Activity Of Farming Of Fragrant Screw Pine ( Pandanus amaryllifolius roxb ) At Subak Tegenungan, Kemenuh Village, Sukawati Subdistrict of   Gianyar Regency Indonesia is a tropical country , because geographically Indonesia traversed by the equator . The geographical position of Indonesia is very supportive the community to conduct agricultural activities . As the largest second contributor to GDP in Bali. Agricultural sector is still done mostly in Subak Tegenungan. The member of Tegenungan Subak from year to year there are convert its land to plant fragrant screw pine . This study aims to find out farm income of the fragrant screw pine , the value of R / C ratio of fragrant screw pine and constraints faced by the farmers . The results showed that farm income of fragrant screw pine equal to Rp 249,656,415.44 per hectare per year . The value of R / C ratio of fragrant screw pine is 5,35 constraints faced by farmers of fragrant screw pine that are in input of urea fertilizer because urea fertililzer subsidized for paddy so that farmers of fragrant screw pine is hard to get it . Keywords : Income of fragrant screw pine